THEORETICAL BASIS OF ORGANIZING STUDENTS' LEARNING ACTIVITIES ON THE BASIS OF PERSONALLY-ORIENTED EDUCATION - Yuldasheva Malokhat Erkinovna; Akramov Mirzaqosim Bakhtiyorjonovna (American Journals, 2024)
This article discusses the essence, didactic possibilities, main directions, principles, and peculiarities of a new view of the personality of the person.
Keywords: Person-Centered education, principle, new approach to the person, democratization of relations, individual approach.